2018
DOI: 10.3390/pr6110230
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Water Absorption and Swelling in Dehulled Barley Grains during Canned Porridge Cooking

Abstract: Understanding the hydration behavior of cereals during cooking is industrially important in order to optimize processing conditions. In this study, barley porridge was cooked in a sealed tin can at 100, 115, and 121 °C, respectively, and changes in water uptake and hygroscopic swelling in dehulled barley grains were measured during the cooking of canned porridge. In order to describe and better understand the hydration behaviors of barley grains during the cooking process, a three-dimensional (3D) numerical mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…The measured WAI (g/g) of the expanded barley RTE snacks ranged between 3.35 and 4.73 g/g (Table 3), which corresponds with results of previous studies (Carvalho et al, 2010;Wang et al, 2018;Wang & Ryu, 2013 et al, 2021;Wang & Ryu, 2013) also showed that the WAI and the expansion index of the extrudates exhibit a strong correlation, which is further explained by the fact that larger porous structures allow more water to enter due to contact with hydrophilic groups. As expected, the WAI slightly increased as the fiber content increased in the raw samples, which was likely due to the hydrophilic nature of the fiber.…”
Section: Wai and Wsi Analysessupporting
confidence: 88%
“…The measured WAI (g/g) of the expanded barley RTE snacks ranged between 3.35 and 4.73 g/g (Table 3), which corresponds with results of previous studies (Carvalho et al, 2010;Wang et al, 2018;Wang & Ryu, 2013 et al, 2021;Wang & Ryu, 2013) also showed that the WAI and the expansion index of the extrudates exhibit a strong correlation, which is further explained by the fact that larger porous structures allow more water to enter due to contact with hydrophilic groups. As expected, the WAI slightly increased as the fiber content increased in the raw samples, which was likely due to the hydrophilic nature of the fiber.…”
Section: Wai and Wsi Analysessupporting
confidence: 88%
“…The moisture content of the rice sample was determined using the standard association of official analytical chemists (AOAC) method ( 26 ). The expansion rate was determined via the drainage method with minor modification, as reported by Pan et al and Wang et al ( 27 , 28 ). Briefly, 50 ml of water was transferred to a 100 ml measuring cylinder.…”
Section: Methodsmentioning
confidence: 99%
“…In this case, it was assumed that the pea remains spherical during hydration (uniform expansion) and behaves as an elastic material, i.e., Hooke’s law was utilized for the stress–strain relationship. Another example involving the mentioned formulation was reported to model water uptake and hygroscopic swelling of dehulled barley grains during cooking of canned porridge [ 106 ]. Again, linear elastic behavior was assumed, but mechanical properties were considered as functions of glass transition temperature.…”
Section: Applications In Various Products/processesmentioning
confidence: 99%